Catastrophism the apocalyptic politics of collapse and rebirth - Lilley, Sasha 1970-; McNally, David 1953-; Yuen, Eddie; Davis, James (PM Press, 2012)
"Amid a global zeitgeist of impending catastrophe, this book explores the culture of fear so prevalent in today's politics, economic climate, and religious extremism. The authors of this collection argue that the lens of catastrophe through which so many of today's issues are examined distorts understanding of the dynamics at the heart of numerous problems, such as global warming, ultimately halting progress and transformation. Arguing that catastrophic thinking results in paralysis or reactionary politics, the authors posit that the myths of 2012 have negative affects across the political spectrum and urge activists not to give up their beliefs and instead focus on working on issues now instead of waiting until society has ended and needs to be rebuilt"--Provided by publisher